2012
DOI: 10.1007/s10389-012-0537-4
|View full text |Cite
|
Sign up to set email alerts
|

Determining the differential preferences of users of two fluoride-free water options in rural Ethiopia

Abstract: Aim In the Ethiopian Rift Valley, 8.5 million people depend on water sources with excessive fluoride. In one rural village, a fluoride-removal community filter was implemented; a personalized reminder was distributed to change people's behavior and increase the usage of the in-village community filter. During this promotion phase, an alternative fluorideremoval option was installed in a neighboring village.This study examines psychological factors that explain the differences in preference between the two opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Again, people engaging in protective behavior should be less susceptible to disease, experience fewer or milder cases, and subsequently rate the impacts on their lives as less severe. This finding is in line with the results of similar studies [48].…”
Section: Discussionsupporting
confidence: 93%
“…Again, people engaging in protective behavior should be less susceptible to disease, experience fewer or milder cases, and subsequently rate the impacts on their lives as less severe. This finding is in line with the results of similar studies [48].…”
Section: Discussionsupporting
confidence: 93%
“…However, more research is needed on the content and delivery of such information to effect sustained behaviour change (Lucas et al . ; Huber & Mosler ) and on evidence‐based behaviour change interventions to more generally improve and sustain water, sanitation and hygiene practices (Fiebelkorn et al . ; Mosler ).…”
Section: Discussionmentioning
confidence: 99%
“…Another case study concerns the area around Lake Lamentation in Kenya fluoride levels ranged between 2.1 and 20.1 mg/l, and fluorosis among children up to age 14 years was 96 %; as 90 % higher than in Dugda district respectively (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…intake from drinking water is 0.03-0.68 mg d -1 and from toothpaste 0.2-0.3 mg d -1 (14,16) Questions regarding water quality showed that people were aware that their water may need to be treated and was intended to do so to minimize health impacts and waterborne diseases. They were also aware of the causes and effects of non-fluoride filtered water quality; however, the some of the community usually has no choice but to use the household level florid filter water they own or the one easily accessible community filter or deemed convenient.…”
Section: Discussionmentioning
confidence: 99%